UPAYA PENINGKATAN PENDAPATAN KELOMPOK USAHA BELUT MELALUI VARIASI HASIL OLAHAN DAN KEMASAN DI GODEAN - -, Sri Palupi; -, Siti Hamidah; -, Yuriani - (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2017)
The purpose of activities include: (1) develop a variation of material processed eel (nuggets, meatballs, and various flavors of snack chips made from eel); (2) participants can describe about entrepreneurship; (3) able to practice manufacturing packaging; (4) the trainees can realize on the sale price and labeling. Implementation method began with a pre-site survey analysis needs a partner to see. After the analysis we needed to know the existence of the problems faced by partners. Of the problems we were trying to find solutions to these problems. The method used in this activity is the lecture method, discussion, and practice. To see the success of the training activities need to be evaluated. As an indicator of the success of both theoretical and practical material 80% of participants can master the training materials. Godean eel business partners could increase the variety processed eel products (nuggets, meatballs, and various flavors of snack chips eel). Godean eel business partners could have the knowledge and understanding of entrepreneurship. Godean eel business partners could make proper and attractive packaging. Godean eel business partners was able to develop labeling that can add to the family income.